ICObench ratings and Initial Coin Offerings’ success - Brochado, A. (2022)
Initial coin offerings (ICOs)–commonly referred to as token sales or token offerings– are assisted by blockchain technology. This financing tool helps entrepreneurs finance early-stage ventures on a decentralized, global scale. Researchers have previously called for more research to be carried out vis-à-vis the role of information intermediaries in the ICO ecosystem. The main goal of this study was to analyze the correlation between ICO ratings and the financing success of ICOs. As a result, secondary microdata on 5,581 ICOs were collected from the ICObench website. The results reveal that ICO ratings issued by third parties have a positive influence on the fundraising campaign of these offerings. ICO ratings thus appear to function as an effective signal to buyers and to reduce information asymmetry between sellers and investors.